Flatbush diabetes – An entity not to be missed- interesting case report (Indian Journal of Case Reports, 2020)
Diabetes is an endocrinological disorder and one of the most common diseases for which admission is warranted. To classify, diabetes is important as various subtypes have different natural history and management. Atypical diabetes or Flatbush diabetes is an entity between Types I and II. Its pathophysiology is poorly understood as the patients usually present with episodes of diabetic ketoacidosis but has glutamic acid decarboxylase antibodies negative and no insulin deficiency. Here, we present an interesting case of atypical diabetes which is an entity not to be missed by clinicians in their practice.